Analisis Pelaksanaan Dan Kesiapan Program Tanam Padi Serentak Dalam Mendukung Ketahanan Pangan : Studi Kasus Di Poktan Sarian Ilir Dusun Jabon Desa Menemeng Kabupaten Lombok Tengah - Rian Aditia; Muhamad Hamzar; Yusril Hamdi; Sudiarti Sudiarti; Al Muslimah; Siti Rohayantini; Iska Nurmayanti; Sri Nadia Mukti Ananta Lewar (Lembaga Publikasi Ilmiah Nusantara, 2025)
National food security has become a top priority in Indonesia’s development policy, particularly in ensuring rice availability as a staple commodity. To address challenges such as population growth, land-use conversion, and fluctuations in rice production, the government launched the Simultaneous Rice Planting Program as a strategy to boost national rice productivity. This program targets 1.3 million hectares across 160 regencies, with an estimated output of 7.5 million tons of unhusked rice by April 2025. This study aims to analyze the implementation and technological preparedness of the simultaneous rice planting system at the Sarian Ilir Farmers Group (Poktan) in Jabon Hamlet, Menemeng Village, Central Lombok Regency as a case study. The region was chosen for its highest rice production rate in West Nusa Tenggara, despite a decline from 52.59 tons/ha in 2023 to 50.51 tons/ha in 2024. This research employed a qualitative case study approach, with data collected through semi-structured interviews, field observations, and documentation. Primary respondents included the Chairperson of Poktan Sarian Ilir, Poktan members, and the Chairperson of the Women Farmers Group (KWT) Jabon Berkarya. The study was conducted on 13.5 hectares of land using agricultural technologies such as Inpari 32 rice variety, legowo row planting system, and an intensive IP3 planting pattern. Program implementation involved collaboration between local government, the Department of Agriculture, Technical Implementation Units (UPT), agricultural extension agents, pest control officers (POPT), security forces (TNI/Polri), and local farmers. The findings are expected to offer a comprehensive evaluation of the program’s effectiveness and provide innovative recommendations to support sustainable food security at both local and national levels.